Nano-technological methods for increasing the oral bioavailability of curcumin - Razieh Nazari; Naghmeh Sattarahmady; Hossein Heli (Fasa University of Medical Sciences, 2017)
Background & Objective: Curcumin is a tropical plant in the ginger (Zingiberaceae) family. Three curcuminoids were from turmeric: Curcumin, demethoxycurcumin, and Bisdemethoxycurcumin. The potential health benefits of curcumin are limited by their poor solubility, hydrophobic property, and low absorption from the gut, rapid metabolism and rapid systemic elimination. Materials & Methods: Scholarly articles were selected using valid keywords and searching on the SID, Google Scholar, PubMed and Elsevier databases. The aim of this paper is to introduce Nano-technological techniques for increasing the oral bioavailability of curcumin. Results: Increase in the drug bioavailability is one of the goals of nanotechnology. Nano-scale materials increase the drug bioavailability due to their unique features. The bioavailability of a drug is defined as a percentage of the initial dose that is independent of the administration route of the drug entering the bloodstream. To improve the bioavailability of curcumin, numerous techniques are used such as curcumin liposome complex, curcumin phospholipid nanoparticles and structural analogues of curcumin. Conclusion: Curcumin has a unique biological and pharmaceutical property. Of course, one of the major limitations of curcumin is its instability and its low solubility. Thus, it is useful to provide a method that can increase the solubility of poorly soluble drugs in water and protect them to achieve the target site. Nanotechnology has provided many ways to improve the solubility and transport of these drugs.